Pengembangan Instrumen Penilaian Berbasis Quizizz Untuk Mengukur Kompetensi Pengetahuan Fisika Siswa - Elisa Elisa; Aslamiyah Rambe; Ainun Mardiyah; Tina Anggaraini Siregar; Roipalah Roipalah; Fatma Zunastri (Journal of Natural Sciences, 2021)
The purpose of this research is to develop a quiz-based assessment tool that can measure students' competence in physics. This research is a type of research on the development of a 4-D model (four-D model) which consists of four stages, namely: definition, design, development and dissemination. The results of the development research got validation results from linguists with an average of 3.57, a percentage of 89% and a "very valid" category. The results of material expert validation with an average of 3.6 percent from 90% and the "very valid" category. The results of media expert validation with an average of 3.4, the percentage of 85% and the "very valid" category. The results of the student observation sheet provide evaluation results of student observations with an average of 15.25% and a percentage of 95.3%. The results of the product capability questionnaire assessment results with the assessed aspects adjusted to the type of product produced with a total of 64 and an average of 3.2 with a proportion of 80% and categorized as "very good". The results of the student response questionnaire on the practicality of students with an average of 54.65, the proportion of 91% and the category "very practical". The results of the student effectiveness questionnaire with an average of 38 percent 95% and the category "very effective".